2007
DOI: 10.1111/j.1439-0396.2007.00723.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet‐induced central obesity and insulin resistance in rabbits

Abstract: The present study was designed to examine whether rabbits fed a diet containing high fat and sucrose could develop obesity and insulin resistance (IR), the major pathophysiological features of metabolic syndrome. Male Japanese white rabbits were fed either a normal chow diet (control) or high fat and sucrose diet (HFSD) for 36 weeks. Plasma levels of triglycerides (TG), total cholesterol (TC), glucose and insulin were measured. To evaluate glucose metabolism, we performed an intravenous glucose tolerance test.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 34 publications
(38 reference statements)
6
56
1
Order By: Relevance
“…Although the use of high-fat diets in rabbits has been reported to induce lipid metabolism disorders and obesity (Antic et al 1999, Zhao et al 2008, Zheng et al 2009), this is not the case in all studies and diets supplemented with fats due to spontaneous reduction of food intake (Armitage et al 2005, Picone et al 2011.…”
Section: Obesitymentioning
confidence: 92%
“…Although the use of high-fat diets in rabbits has been reported to induce lipid metabolism disorders and obesity (Antic et al 1999, Zhao et al 2008, Zheng et al 2009), this is not the case in all studies and diets supplemented with fats due to spontaneous reduction of food intake (Armitage et al 2005, Picone et al 2011.…”
Section: Obesitymentioning
confidence: 92%
“…Several lines of research have reported that this model displays insulin resistance, as well as mildly impaired insulin secretion, both of which are distinct characteristics of the metabolic disturbances observed in patients with T2DM compared to the characteristics observed in monogenetic rodent models of diabetes/obesity or dietary-induced obese rats and mice. 27,28) Compared to the control mice, the mice with STZ-/HFD-induced T2DM showed elevated blood glucose levels; however, treatment with DME (5, 25, or 50 mg/kg) decreased blood glucose levels in a dosedependent manner (Table 2). Further, compared to the controls, the mice with T2DM showed significantly elevated serum total cholesterol and triglyceride levels.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, specific fatty acid profiles of each fat depot should be taken into account when using the rabbit as an animal model of central obesity (Caroll et al, 1996;Zhao et al, 2008;Georgiev et al, 2011;Ivanova et al, 2015;Niimi et al, 2016). For this reason, the omental depot was included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, the New Zealand rabbit is a preferred animal model, widely used to study visceral obesity, atherosclerosis (Yanni, 2004), metabolic syndrome and insulin resistance (Mitsuguchi et al, 2008;Zhao et al, 2008;Georgiev et al, 2011;Ivanova et al, 2015;Niimi et al, 2016). In rabbits, not only the visceral, but also the subcutaneous fat is formed in depots (Cinti, 2005).…”
Section: Discussionmentioning
confidence: 99%